Implementasi Algoritma Golomb Code Dalam Mengkompresi Record Database - Sihaloho, Dumariana (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
In this digital era, everything is digital-based and many applications have been created to make all work easier or used as a means of entertainment. Several existing applications currently have a database as a place to store their data. Currently, the database that is still frequently used is MySQL, this is because MySQL is an open source database server application. The data in the database is called records, the more records stored, the larger the size of the database. The design of this system consists of several main processes, namely the compression process and decompression process as well as the performance calculation process for Compression Ratio (CR), Ratio of Compression (RC), Rendudancy (RD), and Space Saving (SS). In this research the author uses the Golomb Code algorithm, a compression technique introduced by Solomon W. Golomb in the 1960s, which is a lossless compression technique, where this algorithm is capable of compressing large capacity data into smaller capacity data and The original data can be reconstructed after decompression. The performance results of the Golomb Code algorithm aim to determine its performance on database records. In this algorithm there are two stages, namely compression and decompression, the compression stage aims to compress the file size and the decompression stage aims to return the file size to its original size. The results of the application that the author carried out manually with the Golomb Code algorithm are Ratio of Compression (RC) = 1.56, Compression Ratio (CR) = 64.04%, Rendudancy (RD) = 35.95%, Space Saving (SS) = 35.96% with the conclusion that the percentage of database record compression results using the Golomb Code algorithm was declared successful.